Obtenção e caracterização de derivados da 1-indanona: um novo e sucinto caminho para imidas mediante o rearranjo de Beckmann de oximas - Bastos, Thiago Roger Fernandes (2019)
1-indanone is the basis for several drugs, including Eranz®, indicated for the treatment of Alzheimer's disease. The structure of 1-indanone allows a series of chemical modifications related to the delivery of diverse results with biological activities. In the present work, its oxime, in responses with fatty acids projecting the obtainment of oxime esters, made possible, unusually, a new method for the delivery of cyclic imides: 1-heptanoyl-3,4-dihydroquinolin-2(1H) -one (1a); 1-decanoyl-3,4-dihydroquinolin-2- (1H)-one (1b); 1-dodecanoyl-3,4-dihydroquinolin-2(1H)-one (1c) and 1-palmitoyl-3,4- dihydroquinolin-2(1H)-one (1d). Cyclic imides are potential specific units in the preparation of products of interest to the chemical and pharmaceutical industries. The formation of products from 1-indanone oxime having N,N'-dicyclohexylcarbodiimide (DCC) as coating agent and 4,4-dimethylaminopyridine (DMAP) as discoveries, occurred in one step. A mechanistic proposal presented in this work involves the Beckmann rearrangement of oximes. The products, detailed in the literature, were obtained with excellent yields and all were characterized by 1H (1H NMR) and 13C (13C NMR) nuclear magnetic resonance spectroscopy and by gas chromatography coupled to mass spectrometry (GC/MS).